2015
DOI: 10.1159/000439182
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error in Patients with Retinopathy of Prematurity after Laser Photocoagulation or Bevacizumab Monotherapy

Abstract: Purpose: To evaluate the refractive development of premature infants with retinopathy of prematurity (ROP) after treatment with laser photocoagulation or intravitreal injection of bevacizumab (IVB). Methods: The medical records of patients with ROP treated between 2003 and 2012 who underwent yearly follow-ups were retrospectively reviewed. Patients with residual ROP abnormalities were excluded. The cycloplegic refraction at 3 years of age, assessed using an autorefractometer, was recorded. Results: In total, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…Previous studies reported that IVB was associated with less myopia than either laser photocoagulation or combined laser and bevacizumab treatment for type 1 ROP, 37,38 and treatment-requiring ROP eyes were susceptible to more severe myopia with age compared with eyes without ROP or those with spontaneously regressed ROP. 39 The intraretinal layer thicknesses in high myopic eyes varied significantly from emmetropic eyes. 40 In addition, laser treatment might alter the thickness of the inner layer of the retina, 41 and such changes should be considered in ROP patients after laser photocoagulation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that IVB was associated with less myopia than either laser photocoagulation or combined laser and bevacizumab treatment for type 1 ROP, 37,38 and treatment-requiring ROP eyes were susceptible to more severe myopia with age compared with eyes without ROP or those with spontaneously regressed ROP. 39 The intraretinal layer thicknesses in high myopic eyes varied significantly from emmetropic eyes. 40 In addition, laser treatment might alter the thickness of the inner layer of the retina, 41 and such changes should be considered in ROP patients after laser photocoagulation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received treatment for ROP were more prone to myopia, regardless of treatment modality. The results suggest that treatment-demanding ROP eyes are susceptible to more severe myopia with age compared with eyes without ROP or those with spontaneously regressed ROP [22].…”
Section: Refractive Outcomesmentioning
confidence: 85%
“…Some series report higher rates of myopia in eyes treated with laser than in those treated with IVB or ranibizumab(35). Other studies report that having type I ROP, compared to non-type 1 ROP or no ROP, was associated with myopia and that outcomes were similar following laser or IVB at 3 years of age(36), whereas still others report posterior disease, compared to peripheral disease, was associated with myopia(34). Lack of statistical significance may be from small sample sizes, and longer follow up is needed to assess refractive outcomes after laser vs. anti-VEGF agents..…”
Section: Introductionmentioning
confidence: 99%